LIMBAH PENYULINGAN SEREH WANGI DAN NILAM SEBAGAI INSEKTISIDA PENGUSIR LALAT RUMAH (Musca domestica) - Sri Usmiati, Nanan Nurdjannah dan Sri Yuliani (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACT The solid waste of citronella and patchouly oil distillation still contain small amount of essential oil especially volatile compound. Both contain volatile and non-volatile components that could be used as active compounds of incense, candle and mosquito repellent. The aim of this study is to find out incense formula of solid waste of citronella and patchouly oil as the insect repellent for Musca domestica. The study was done at Indonesian Center for Agricultural Postharvest Research and Development, Bogor. The experiments were designed as Completely Randomized Design with 4 combination treatments and 3 replications. The results showed that the solid waste of citronella and patchouly oil distillation can be used as the active compounds of incense insect repellent. The best formulas are F3 and F4 that consist of 4:4 and 5:3 of the solid waste from citronella and patchouly respectively. Those formulas have 100% repellent activity in 2 and 3 hours burning period respectively. Key words: citronella, patchouly, insectisidal, effetivity